Comparison of the Modified Chinese Baecke Questionnaire With a 3-Day Activity Diary in a Hong Kong Chinese Population. (March 2015) - Ho, Suzanne C.; Yu, Ruby; Chan, Sophie
The aim of this study was to determine the reliability and validity of the modified Chinese Baecke Questionnaire, using a 3-day activity diary as a reference, in Hong Kong Chinese population. A total of 198 Chinese subjects aged 18 to 65 years were recruited in Hong Kong. Validity of the questionnaire was assessed using a 3-day activity diary as the reference method. Two-week test–retest reliability was also evaluated. Good reliability for the modified Chinese Baecke Questionnaire was demonstrated (correlation coefficients ranged from 0.65 to 0.90). Cohen's κ was 41.0% for men and 56.7% for women. High correlation between the weighted total index computed from the questionnaire and daily energy expenditure obtained from the diaries ( r = 0.61) was demonstrated ( r = 0.56, P < .01 for men and r = 0.59, P < .01 for women). Overall, 2.1% and 4.8% gross misclassifications were found for men and women, respectively. In conclusion, the modified Chinese Baecke Questionnaire was found to be reliable and valid for measuring habitual physical activity in the Hong Kong Chinese adult population.